2009
DOI: 10.2220/biomedres.30.129
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of bonito extract ameliorates peripheral blood flow in mice loaded from over crowding stress

Abstract: Bonito extract (BE) has been shown to improve various fatigue-related symptoms. The possibility that the improvement of blood flow contributes to the improvement of fatigue-related symptoms has been reported. However, even though BE has been found to increase peripheral blood flow in humans, an understanding of its mechanisms has remained elusive. The purpose of the present study is to construct an animal model system with which the blood flow-increasing effects of BE can be examined. Using mice loaded with cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Interestingly, in terms of its mechanism, it has been reported that the ingestion of bonito broth increases peripheral blood flow in humans, 9 resulting in an antioxidative effect and an improvement in mood. 9 , 12 In addition, an increase in the cerebral blood flow in mice 10 and rats 11 has been evidenced in the groups ingesting bonito broth, resulting in a decrease in stroke in hypertensive rats. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in terms of its mechanism, it has been reported that the ingestion of bonito broth increases peripheral blood flow in humans, 9 resulting in an antioxidative effect and an improvement in mood. 9 , 12 In addition, an increase in the cerebral blood flow in mice 10 and rats 11 has been evidenced in the groups ingesting bonito broth, resulting in a decrease in stroke in hypertensive rats. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Vascular damage from SOR has also been reproduced in the vascular area dimension of GFP-labeled vessels in the transgenic medaka model 5. HIS, the major component among the amino acids contained in the bonito extract,11 alleviated this vascular damage in the medaka fin by maintaining the vascular area dimension without growing new vessels and exhibited no tumor cell growth 5. The results from an animal model and in vitro study have suggested that DBB and HIS may contribute to the maintenance of blood flow with no evidence of tumor growth.…”
Section: Discussionmentioning
confidence: 90%
“…Honda and others () suggested that ingestion of BF decreases oxidative stress in humans and that the BF may have antioxidative effects. Lukas and others () indicated that ALP activity and the level of thiobarbituric acid reactive substances were mutually decreased by dietary fish oils containing 0.2% DHA.…”
Section: Resultsmentioning
confidence: 99%
“…Bonito ( Katsuwonus pelamis ) is a medium‐sized, predatory fish of the genus Sarda , in the mackerel family. BF is used as one of the most traditional food ingredients in Japan, and many nutritional benefits have been reported (Matsumoto and others ; Nozawa and others ; Honda and others ). Our previous data have shown increases in bone mass and bone strength in growing Wistar rats fed with a BF diet compared with a casein diet (unpublished data).…”
Section: Introductionmentioning
confidence: 99%